Legal Protection of Song Copyrights in Digital Form - Chrisna Arwiandra Leuwol; Ludevikus Limdianda; Arjuna Rizky Dwi Krisnayana (Universitas Airlangga, 2020)
The development of advanced technology and faster, ease of accessing the virtual world leads to equal public access to information collected on the internet, one of which is a song, a recording of rhythmic sound that was originally shaped physics from the record vinyl then to become a tape cassette for radio tape and now evolved along with technology into digital media like DVD, Flash disk, and Hard disk. The Internet connects the global world to a single location. Based on this case KEMENKOMINFO (Ministry of Communication and Informatics) has attempted to enforce the closure of a number of sites that commit illegal acts such as uploading, downloading and reproduction of songs on the internet without the permission of the author and copyright holder. From the problematic law is written this thesis about copyright protection of songs on the internet, what the copyright standards of songs on the internet together with the form of copyright infringement of songs on the internet and recovery efforts.